ANALYSIS OF RELIABILITY & AVAILABILITY OF GENERATOR SET MACHINE (GENSET) OF POLYTECHNIC AVIATION SURABAYA - Surya Widdana; Hartono Hartono; Tekat Sukomardojo (Politeknik Penerbangan Surabaya, 2025)
Generator sets (generators) are backup power sources that have an important role in maintaining operational and service continuity at the Surabaya Aviation Polytechnic when there is a disruption of electricity supply from PLN. The reliability and availability of generators are the main factors that determine the sustainability of educational activities, practicums, and campus facility operations. This study aims to analyze the reliability and availability of the Cummins Silent 500 KVA Generator Set engine based on operational and maintenance data during the January-December 2024 period. The study used a descriptive quantitative approach by utilizing data on operating hours, scheduled maintenance times, repair times due to damage, and number of component failures. The analysis was carried out using the indicators of Specified Operating Time (SOT), Actual Operating Time (AOT), Mean Time Between Failures (MTBF), Reliability, and Availability. The results showed that the average reliability level of Generator Set 1 was 98.90%, while Generator Set 2 was 99.15%. The largest decrease in reliability occurred in Generator Set 1 in June with a value of 94.47%, which was caused by damage to several components thus increasing repair time. Meanwhile, the average availability rate of Generator Set 1 and Generator Set 2 reached 95.10% and 95.24%, respectively, indicating that both units still have a good level of operational readiness. The results of this study can be the basis for the preparation of preventive maintenance strategies and equipment performance evaluations to improve the reliability and continuity of electrical power supply at the Surabaya Aviation Polytechnic.